(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The Karbi tribe is one of the major ethnic groups in northeast India, belonging to the Tibeto-Burman linguistic family, and is among the oldest inhabitants of Assam. The Karbis living in the plains of Assam are referred to as dumrali or plain Karbis. They are known to have a high sense of reverence and pride towards their aspect of inherent masculinity. The word Karbi signifies a sense of brotherhood. The Karbi tribe, indigenous to Kamrup Metro in Assam, India offers a wealth of traditional knowledge and practices in sustainable resource management, which have been integral to their way of life for generations. The Karbis of the Dimoria region live alongside and coexist with various other communities. This paper explores how the Karbi indigenous practices, deeply rooted in their cultural and spiritual beliefs, promote environmental conservation and sustainable use of natural resources. Their shifting cultivation (jhum), community-based forest management and water conservation techniques demonstrate a profound understanding of ecological balance. These practices not only maintain biodiversity but also ensure the sustainability of resources for future generations. By blending traditional ecological knowledge with modern sustainability initiatives, the Karbi tribe’s practices provide valuable insights into managing natural resources in a manner that is both environmentally sustainable and culturally respectful.